The Challenges of English Language Teaching in Multilingual Classroom - Fauzan Najib; Muhammad Ilham; Nurul Fadhillah, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The utilization of informal language, commonly referred to as slang, constitutes a dynamic and ever-changing social phenomenon, reflecting the intricate interplay between language and culture. This research study delves into the specific manifestations of slang nomenclature found in the cinematic work "Django Unchained." To achieve this, the study adopts the classifications outlined by renowned linguists Bloomfield (1933) and Guth (1962). Through meticulous analysis, the research discerns five distinct categories of slang employed within the film: abbreviations (such as "O.B." signifying an individual's initials), truncated forms (for instance, "kinda" in lieu of "kind of"), interjections (like "bravo," used to convey approval), figurative expressions (such as "goddamn," indicating frustration), and nicknames (like "fancy pants," used to mock someone's attire). The prevalent linguistic feature observed in the film is the use of shortened forms, highlighting a penchant for succinct communication within casual environments. Abbreviations are infrequently utilized, implying the movie's adherence to a more formal discourse. Notably, the absence of comical mispronunciations among the characters indicates precise pronunciation. This analytical examination provides valuable insights into the varied linguistic evolutions present within slang, underscoring its malleability and its responsiveness to societal influences.